Penerimaan Teknologi Sistem OSS di DPMPTSP Kabupaten Nagan Raya - Cut Enna Febrianda (Universitas Teuku Umar, 2023)
Information technology helps make the public service process much faster and more precise. The same service also forces service users to adapt to the computing and information programs offered by the service provider, making it easier for them to receive the services they want. OSS is a solution for licensing service users to get their services without attending the DPMPTSP office. This research wants to see how far service users can adapt to the OSS program and whether they feel comfortable with it. The results of the 73 research samples in this study showed that PU has a beta coefficient more significant than the PEOU variable in predicting attitudes towards using OSS. This means that the information system developed by the government has a high acceptance level because users must prioritize the usefulness of the system that has been developed from the previous system.